Hadrian’s aqueduct in Athens: Educational activity project in the context of promoting cultural heritage among youth - Alexandri, Eleni; Tranta, Alexandra (Journal of Integrated Information Management, 2024)
Purpose: To contribute to the study of cultural heritage, as well as to explore the possibility of delving deeper into a number of its fields through a single monument. Design/methodology/approach: Applying contemporary informal education approaches to the design of an educational program for cultural monuments taking Hadrian’s aqueduct as the starting point. Findings: The rich interdisciplinary approach that emerged from the study of a single monument, its capacity to “narrate” stories as well as the potential of its gainful employment by young people, aiming at their cultural awareness concerning world cultural heritage of monuments. Practical value: understanding and applying learning theories for studying objects, realizing the degree to which discussing objects contributes to and illuminates different aspects of material culture, given that learning is influenced by personal elements, too: one’s interests, inclinations, the manner in which one prefers to learn, etc. Originality/value: Examining how a monument of cultural heritage can be perceived through a broader and more interesting feel for its inherent meaning, instead of exclusively through its narrow morphological sense, remains relevant.